O licenciamento ambiental e a atuação do poder público na realização do aterro hidráulico da Praia de Iracema - Melo, Juliana Barroso de (2005)
The occupation of the costal area in Fortaleza along the last two decades has had touristic trade as the main segment. As a consequence there has been the fast occupation of this area by enterprise buildings besides other construction work aiming to make the coastal area more suitable for the demands of the touristic trade. As an example we mention the praia de Iracema hydraulic embankment (aterro hidráulico) that has caused negative impact on the coastal ecosystem such as interference on the dynamic of the tides as well as damage on the characteristics of the coastal landscape. According to the title “Environmental licensing and interventions of the Public Power on the coastal area of Fortaleza – Ceará: considerations on the praia de Iracema hydraulic embankment” this research work aims to show the importance of environmental licensing as a means to control the accomplishment of public as well as private construction work and consequently the better occupation of the coastal area along Fortaleza. The lack of an adequate ordering in the use and occupation of the coastal urban area along Fortaleza tends to maximize the problem of its exaggerated use thus causing damage to the environmental resources. It is crucial the development of preventive public policies aiming a better ordering and planning of the use of the coastal urban space allowing the preservation of natural resources and giving more guarantee to the sustainability of the economical activities, mainly tourism. For all these reasons and having in mind the ideal of sustainability of the coastal areas of the cities it is fundamental that the Public Power take good care of the established law and make use of preventive instruments such as the previous study of environmental impactand environmental licensing where all parts be effectively integrated and aiming the maintenance of good living conditions.